Food Hygiene Practices and Foodborne Disease Risks Among Students and Food Handlers in Sarawak Rural Schools - Ling, Song Jing; Regina Garai, Abdullah; Zamri, Hassan (RSIS International, 2026)
Foodborne diseases account for millions of deaths globally. Key factors contributing to these illnesses, as well as the high incidence of food poisoning among students, include improper methods of food preparation, unhealthy lifestyles, poor sanitation, and unsafe water resources. Moreover, poor food-handling practices for food handlers, combined with insufficient food hygiene knowledge among both handlers and students, significantly increase the risk of food poisoning in school environments. This paper discusses the knowledge, attitudes, and practices (KAPs) regarding food hygiene among food handlers and students, based on findings from a quantitative study employing a non-probability quota sampling method. The sample comprised 487 students and 23 canteen food handlers drawn from eight selected schools (five primary schools and three secondary schools) in Betong, Sarawak, Malaysia. These schools were selected due to their high incidences of food poisoning. Findings indicated that the food handlers demonstrated poor personal hygiene practices, including improper handwashing technique and limited knowledge about the correct steps needed for effective handwashing. In addition, the food safety conditions associated with the canteen environment were found to be statistically significant, and differences in food hygiene knowledge were observed between male and female food handlers. Furthermore, students demonstrated low awareness of cross-contamination risks, particularly regarding the inappropriate use of the same towel for wiping hands and plates. Overall, this research provides valuable insights and highlights the need for behavioural changes that could inform national health policy revisions, particularly in the area of food safety and regulations for preventing food poisoning.